Feasibility and acceptability of at-home play kits for middle school physical activity promotion during the COVID-19 pandemic - Emily Kroshus; Kiana Hafferty; Kimberly Garrett; Ashleigh M. Johnson; Leighla Webb; Andrew Bloom; Erin Sullivan; Kirsten Senturia; Pooja S. Tandon (BMC, 2023)
Abstract Background Schools are central to providing opportunities for youth physical activity (PA), however such opportunities were limited during the COVID-19 pandemic. Identifying feasible, acceptable, and effective approaches for school-based PA promotion amid pandemic-related barriers can inform resource allocation efforts in future circumstances necessitating remote instruction. The aims of this study were to: (1) describe the pragmatic, stakeholder-engaged and theory-informed approach employed to adapt one school's PA promotion efforts to pandemic restrictions, leading to the creation of at-home "play kits" for students, and (2) assess the feasibility, acceptability, and preliminary effectiveness of this intervention. Methods Intervention activities occurred in one middle school (enrollment: 847) located in a Federal Opportunity Zone in the Seattle, WA area, with control data from a nearby middle school (enrollment: 640). Students at the intervention school were eligible to receive a play kit during the quarter they were enrolled in physical education (PE) class. Student surveys were completed across the school year (n = 1076), with a primary outcome of days/week that the student engaged in ≥ 60 min of PA. Qualitative interviews (n = 25) were conducted with students, staff, parents, and community partners, and focused on play kit acceptability and feasibility. Results During remote learning play kits were received by 58% of eligible students. Among students at the intervention school only, students actively enrolled in PE (versus not enrolled) reported significantly more days with ≥ 60 min of PA in the previous week, however the comparison between schools was not statistically significant. In qualitative interviews, most students reported the play kit motivated them to participate in PA, gave them activity ideas, and made virtual PE more enjoyable. Student-reported barriers to using play kits included space (indoors and outdoors), requirements to be quiet at home, necessary but unavailable adult supervision, lack of companions to play outdoors, and inclement weather. Conclusions A pre-existing community organization-school partnership lent itself to a rapid response to meet student needs at a time when school staff and resources were highly constrained. The intervention developed through this collaborative response-play kits-has potential to support middle school PA during future pandemics or other conditions that necessitate remote schooling, however modifications to the intervention concept and implementation strategy may be needed to improve reach and effectiveness.